The Role Of Silek In Traditional And Modern Dance In Minangkabau - Venny Rosalina; Solfema; Hadiyanto; Nurhizrah Gistituati; Mega Iswari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This paper discusses the role of silek in the development of dance in Minangkabau. Silek became the root in the creation of dance movements. Starting from traditional dances such as pasambahan dance, galombang dance, piriang dance, to modern dance with a contemporary style. Every aspect of the initial movement to the final movement, Minangkabau dance is inseparable from the silek element that dominates and becomes a characteristic. Although the pattern of modernity affects the social life of the community, it does not change the belief in shifting the existence of silek in the creation of Minangkabau dance works. This study examines how important silek is in dance in Minangkabau. Through qualitative research methods, it will be seen from every aspect of silek and its development by observation, observation and interview. The development of dance in Minangkabau is seen from the intensity of society which always develops silek on dance and makes dance a medium to express meaning in the order of life.